Examination of repeated sprinting ability and fatigue index of soccer players according to their positions - Kaplan, T. (The Journal of Strength and Conditioning Research, 2010)
The aim of this study is to evaluate repeated sprinting ability and fatigue index of amateur soccer players according to their positions. A total of 85 amateur soccer players were examined in different clubs in Turkey. The repeated sprint test, which was designed by Bangsbo, was used for soccer players. We did not find any statistical differences for repeated sprints, best time, average time, and fatigue index values according to positions of soccer players (p > 0.05). On the other hand, there was a statistical difference between 7 maximal sprints for the defense players, midfielders, and forwards (p < 0.05) but there was not a statistical difference between 7 maximal sprints for the goalkeeper (p > 0.05). In conclusion, it is considered that speed at soccer is very important and there must be fast moving players in all positions. This study reveals that defense players, midfielders and forwards are able to maintain 5 repeated sprints at the same compactness during the match. For goalkeepers, it could not be found any difference at the repeated sprints. It is considered that on choosing or transferring players, the trainers must take into account their sprint abilities. But repeated sprints are not a specific indicator for goal keepers, and this characteristic should not be used for the choice of goalkeepers. In addition, the players' ability of managing to do several repeated sprints at the same compactness during the match should be pursued by the trainers. And it should be given place to the repeated sprint exercises in the training schedules.